Modern acoustical techniques for the measurement of mechanical properties - Levy, Moises; Bass, H. E. (Henry E.); Stern, Richard R. (Experimental methods in the physical sciences, 2001)
This volume provides an overview of modern acoustical techniques for the measurement of mechanical properties. Chapters include Fundamentals of Elastic Constants; Point Source/Point Receiver Methods; Laser Controlled Surface Acoustic Waves; Quantitative Acoustical Microscopy of Solids; Resonant Ultrasound Spectroscopy; Elastic Properties and Thermodynamics; Sound Speed as a Thermodynamic Property of Fluids; Noninvasive Determination of Sound Speed in Liquids; Introduction to the Elastic Constants of Gases; and Acoustic Measurement in Gases.